Perlindungan Melalui Hukum Pidana Terhadap Kerahasiaan Identitas Diri Anak Korban - Teuku Renardi Idfidian; Ade Adhari (LPPM Universitas Ekasakti Padang, 2023)
Sexual violence reported in print and online media has both negative and positive impacts on victims of sexual violence. The identity of child victims must be kept confidential from the public. A child's identity that is not kept confidential can have a negative impact on child victims, especially child victims of sexual violence. The name of the Child Victim, which should be kept confidential, can be found in the Court Decision which can be accessed on the Supreme Court Directory Website (putusan3.mahkamahagung.go.id). The decision mentions details about the incident of sexual violence that is directly related to the Child Victim of sexual violence. For violation of this prohibition, the perpetrator should be subject to punishment according to applicable regulations.